Synthesis and properties of multiscale porosity TiC-SiC ceramics. Issue 8 (July 2019) - Baux, A.; Nouvian, L.; Arnaud, K.; Jacques, S.; Piquero, T.; Rochais, D.; David, P.; Chollon, G.
Abstract: A process combining the pyrolysis of a lignocellulosic structure and reactive gas treatments has been developed to prepare porous TiC-SiC ceramics for solar receivers. The natural micro-porosity of balsa was complemented by a high open macro-porosity by laser cutting a periodical arrangement of parallel channels. The lignocellulosic structure was first pyrolysed into carbon. This reactive carbon material was then converted into TiC by Reactive Chemical Vapor Deposition (RCVD) using TiCl4 /H2 . After controlling the absence of cracks due to volume changes, the TiC structure was finally infiltrated by the Chemical Vapor Infiltration (CVI) of SiC using CH3 SiCl3 /H2 . The density, porous structure, elemental and phase compositions, oxidation behavior and crushing strength were assessed after pyrolysis, RCVD and CVI. The SiC CVI coating significantly improves the compressive strength, the oxidation resistance and the thermal properties. The SiC layer is no longer fully protective at high temperature but the mechanical properties remain reasonably high.